Magnetocaloric effect and spin-strain coupling in the spin-nematic state of LiCuVO_{4} - M. Gen; T. Nomura; D. I. Gorbunov; S. Yasin; P. T. Cong; C. Dong; Y. Kohama; E. L. Green; J. M. Law; M. S. Henriques; J. Wosnitza; A. A. Zvyagin; et al. (Physical Review Research, 2019)
We report on the magnetocaloric effect and ultrasound studies of the frustrated quasi-one-dimensional spin-1/2 compound LiCuVO_{4}, evidencing a spin-nematic state. The magnetic Grüneisen parameter diverges at the transition to the spin-nematic phase, μ_{0}H_{c3}≈40 T, showing quantum criticality accompanied by entropy accumulation. The observed high-field anomalies in the acoustic properties clearly evidence a strong involvement of the lattice in the spin dynamics. The theoretical approach, based on exchange-striction coupling with dipolar and quadrupolar contributions, suggests that the spin-dipole-strain and quadrupole-strain interactions govern the spin-nematicity in LiCuVO_{4}.